2007
DOI: 10.1103/physrevlett.98.190401
|View full text |Cite
|
Sign up to set email alerts
|

Generating Unexpected Spin Echoes in Dipolar Solids withπPulses

Abstract: NMR spin echo measurements of 13C in C60, 89Y in Y2O3, and 29Si in silicon are shown to defy conventional expectations when more than one pi pulse is used. Multiple pi-pulse echo trains may either freeze out or accelerate the decay of the signal, depending on the pi-pulse phase. Average Hamiltonian theory, combined with exact quantum calculations, reveals an intrinsic cause for these coherent phenomena: the dipolar coupling has a many-body effect during any real, finite pulse.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…(4), no long-lived echoes are predicted (as shown from simulations), and if H cs = 0, the effects of a CPMG(φ 1 , φ 2 ) pulse train is identical to that from the corresponding Hahn echo experiments in dipolar solids. As mentioned in the introduction, previous theories for observing long-lived echoes require imperfect π−pulses, either through consideration of dipolar evolution during the pulse 16,17 or due to field inhomogeneites that render the applied pulse imperfect [20][21][22] . While including H D during the pulse would definitely be needed if the interpulse spacing, 2τ , was comparable to the π−pulse time, t p = (2)].…”
Section: Theory and Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4), no long-lived echoes are predicted (as shown from simulations), and if H cs = 0, the effects of a CPMG(φ 1 , φ 2 ) pulse train is identical to that from the corresponding Hahn echo experiments in dipolar solids. As mentioned in the introduction, previous theories for observing long-lived echoes require imperfect π−pulses, either through consideration of dipolar evolution during the pulse 16,17 or due to field inhomogeneites that render the applied pulse imperfect [20][21][22] . While including H D during the pulse would definitely be needed if the interpulse spacing, 2τ , was comparable to the π−pulse time, t p = (2)].…”
Section: Theory and Numerical Simulationsmentioning
confidence: 99%
“…Such observations are reconfirmed in Figs There have been two main theoretical proposals to understand the long-lived spin echoes under CPMG pulse trains. One explanation, propounded by the Barrett group [16][17][18] , which we refer to in throughout the paper as the Barrett proposal, is that these long-lived echoes are a consequence of resonance offset and dipolar evolution during the π−pulse, i.e., the π−pulses cannot be treated as pure δ-pulses. Using average Hamiltonian theory 19 (AHT), these authors demonstrated that the CPMG(φ 1 , φ 2 ) generates an effective field that, depending on the π pulse phases, φ 1 and φ 2 , can spin-lock the magnetization after an initial π 2 X pulse; it was argued 17 that this effect was not equivalent to pulsed spin-locking.…”
Section: Introductionmentioning
confidence: 99%
“…In all the samples mentioned already, the spin-spin decay time measured with a Hahn echo sequence (T HE 2 ) [34] was about an order of magnitude longer than the FID characteristic time (T * 2 ), evidencing the line inhomogeneity. Magnetization tails have been observed in 29 Si, C 60 and Y 2 O 3 [13,41,42], in adamantane under 1 H decoupling [57] and indirectly in 31 P in EPR experiments [20].…”
Section: Long-lived Signalsmentioning
confidence: 96%
“…We summarize our own findings on anomalous long-lived echo signals [12,[41][42][43][44]. In particular, we emphasize the use of a simple stimulated echo sequence to discern whether one is in the presence of true long decoherence times or if the coherences are being saved as polarization and then recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Using expression (23) for the truncated dipolar Hamiltonian, it is possible to split this expression in two parts:…”
mentioning
confidence: 99%